Earth's oldest mantle fabrics indicate Eoarchaean subduction - Kaczmarek, M.; Reddy, Steven; Nutman, A.; Friend, C.; Bennett, V. (Macmillan Publishers Limited, 2016)
The extension of subduction processes into the Eoarchaean era (4.0-3.6 Ga) is controversial. The oldest reported terrestrial olivine, from two dunite lenses within the ~3,720 Ma Isua supracrustal belt in Greenland, record a shape-preferred orientation of olivine crystals defining a weak foliation and a well-defined lattice-preferred orientation (LPO). [001] parallel to the maximum finite elongation direction and (010) perpendicular to the foliation plane define a B-type LPO. In the modern Earth such fabrics are associated with deformation of mantle rocks in the hanging wall of subduction systems; an interpretation supported by experiments. Here we show that the presence of B-type fabrics in the studied Isua dunites is consistent with a mantle origin and a supra-subduction mantle wedge setting, the latter supported by compositional data from nearby mafic rocks. Our results provide independent microstructural data consistent with the operation of Eoarchaean subduction and indicate that microstructural analyses of ancient ultramafic rocks provide a valuable record of Archaean geodynamics.